Abundance and temperature of the outer hot circumgalactic medium: The SRG/eROSITA view of the soft X-ray background in the eFEDS field - Ponti, G.; Zheng, X.; Locatelli, N.; Bianchi, S.; Zhang, Y.; Anastasopoulou, K.; Comparat, J.; Dennerl, K.; Freyberg, M.; Haberl, F.; Merloni, A.; Reiprich, T. H.; et al. (Astronomy & Astrophysics, 2023)
Context. Despite their vital importance to understanding galaxy evolution and our own Galactic ecosystem, our knowledge of the physical properties of the hot X-ray emitting phase of the Milky Way is still inadequate. However, sensitive SRG/eROSITA large area surveys are now providing us with the long-sought data needed to mend this state of affairs. Aims. Our aim is to constrain the properties of the Milky Way hot halo emission toward intermediate Galactic latitudes close to the Galactic anti-center. Methods. We analyzed the spectral properties of the integrated soft X-ray emission observed by eROSITA in the relatively deep eFEDS feld. Results. We observe a flux of 12.6 and 5.1 × 10-12erg cm-2s-1deg-2in the total (0.3-2) and soft (0.3-0.6 keV) band. We measure the temperature and metal (oxygen) abundance of the hot circumgalactic medium (CGM) to be within kTCGM = 0.153-0.178 keV and ZCGM = 0.052-0.072 Z·, depending on the contribution of solar wind charge exchange (SWCX). Slightly higher CGM abundances ZCGM = 0.05-0.10 Z·are possible, considering the uncertain extrapolation of the extragalactic cosmic X-ray background (CXB) emission below ∼1 keV. To recover CGM abundances as high as ZCGM = 0.3 Z·, the presence of an additional component must be postulated, likely associated with the warm-hot intergalactic medium, providing ∼15-20% of the flux in the soft X-ray band. We observe line widths of the CGM plasma smaller than δv = 500 km s-1. The emission in the soft band is dominated (∼47%) by the circumgalactic medium (CGM), whose contribution reduces to ∼30% if heliospheric SWCX contributes at the level of ∼15% also during solar minimum. The remaining flux is provided by the CXB (∼33%) and the local hot bubble (∼18%). Moreover, the eROSITA data require the presence of an additional component associated with the elusive Galactic corona plus a possible contribution from unresolved M dwarf stars. This component has a temperature of kT ∼ 0.4- 0.7 keV, a considerable (∼ kiloparsec) scale height, and might be out of thermal equilibrium. It contributes ∼9% to the total emission in the 0.6-2 keV band, and is therefore a likely candidate to produce part of the unresolved CXB flux observed in X-ray ultra-deep felds. We also observe a signifcant contribution to the soft X-ray flux due to SWCX, during periods characterized by stronger solar wind activity, and causing the largest uncertainty on the determination of the CGM temperature. Conclusions. We constrain temperature, emission measure, abundances, thermal state, and spectral shape of the outer hot CGM of the Milky Way.
CRIS-Team Scopus Importer:2023-09-01
Keywords: Galaxy: abundances; Galaxy: halo; ISM: general; ISM: structure; Local insterstellar matter; X-rays: diffuse background